2021
DOI: 10.21037/gs-20-725
|View full text |Cite
|
Sign up to set email alerts
|

Lateral approach improves surgical access to the superior pole in giant endemic goiters

Abstract: Background: Surgical management of mega-goiters in endemic areas with extreme iodine deficiency presents unique challenges. Based on our initial 5-year experience (2007 to 2011) operating on mega-goiters in Gitwe, Rwanda, Africa, we modified our technique to a lateral approach which affords better exposure of the superior pole vessels and other vital neurovascular structures, thereby improving safety. We describe this lateral approach technique and review outcomes compared to the standard technique Methods: Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The publications covered STSTs from 1989 to 2021, with one study from the 1980s, 18 five from the 1990s, 19–23 15 from the 2000s, 24,25,34–38,26–33 and 26 from 2010 to 2021 39,40,49–58,41,59–61,42–48 . The average study period was 4.14 years with a range of one week to 25 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The publications covered STSTs from 1989 to 2021, with one study from the 1980s, 18 five from the 1990s, 19–23 15 from the 2000s, 24,25,34–38,26–33 and 26 from 2010 to 2021 39,40,49–58,41,59–61,42–48 . The average study period was 4.14 years with a range of one week to 25 years.…”
Section: Resultsmentioning
confidence: 99%
“…Head and neck surgery studies are more heterogenous, consisting mostly of thyroids and free flap reconstructions. A thyroid study that presented a new technique to treat massive goiter found complication rates comparable to traditional thyroidectomy in similar LMIC cohorts, suggesting that this technique could be considered as an alternative 46 . However, small sample sizes, author biases, and short‐term follow‐up may limit the generalizability of these conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations